Characteristics of the obstetric patient in critical stage in Cienfuegos province. - Bárbara Lucía Cabezas Poblet; Yoel Valle; María Antonia Cabezas Poblet; Esteban Hernández Barrios; Rolando T. Espín González (Medisur)
Fundaments: The critically ill patient has an important place in the assessment of the quality of the medical assistance since around 5 % of all females who reach a full term pregnancy without potential risk factors, become this kind of patients due to different causes. Objective: To characterize the obstetric patient in a critical state in the period that covers January 1 st 1991- December 31 st 2001 in Cienfuegos province. Method: Correlational Descriptive-retrospective study carried out at the ICU of the Clinico-Surgical University Hospital ¨Dr. Gustavo Aldereguía Lima¨ in a 10 year period and includes the 323 critically ill obstetric patients who were admitted at that ward. The variables under study were: mother´s age parity, type of labor, past history, surgical procedures, cause of admission at the ICU, patients state at discharge and cause of death. Results: 59,1 % of the patients were aged 20-29 years . The patient´s past history was related to hypertension and bronchial asthma. The procedure most widely used was the cesarean section followed by hysterectomy as emergency. The principal cause of admission at the ICU was hypovolemic shock, pre eclampsia - eclampsia and sepsis. The major amounts of patients were discharged alive. Only 8 % died. There was a predominance of direct maternal death, highlighting among them haemorrhage and hypertension in pregnancy.